Cytotoxicity and estrogenicity in simulated dental wastewater after grinding of resin-based materials. Issue 10 (October 2021) - Reidelbach, C.; Garcia-Käufer, M.; Wingert, N.; Arif, A.; Vach, K.; Hellwig, E.; Gminski, R.; Polydorou, O.
Highlights: Grinding of resin-based dental materials results in pollution of wastewater. Components of resin-based dental materials cause bactericidal and cytotoxic effects. Eluates of resin-based dental materials seem not to exert estrogenic effects. Abstract: Objective: This study evaluated the cytotoxic and estrogenic effects of dust and eluates released into simulated wastewater after grinding of dental resin-based materials. Methods: Four materials were used: ceram.x® universal, Filtek™ Supreme XTE, Lava™ Ultimate and Core-X™ flow. From each composite material, samples (5 × 2 mm, n = 50) were prepared according to the manufacturers' instructions. Lava™ Ultimate was used as blocks. All samples were ground to dust with a diamond bur (106 μm) and suspended in distilled water at 60 mg/mL. After storage for 72 h, the suspensions were separated into a soluble (eluate) and a particulate (dust) fraction. Eluates and dusts were evaluated for inhibition of Vibrio fischeri bioluminescence and cytotoxicity on human A549 lung cells (WST-1-Assay). The estrogenic activity was assessed by YES-Assay using Saccharomyces cerevisiae. Additionally, dental monomers (BisGMA, BisEMA, UDMA, TEGDMA, HEMA) and Bisphenol A were investigated. Results: All eluates showed inhibition of V . fischeri bioluminescence at concentrations above 1.1 mg/mL (p < 0.05). The activity of the eluates of ceram.x® universal and Filtek™ Supreme XTE was significantly higher than Lava™ Ultimate and Core-X™ flow (p < 0.05). In the WST-1-Assay, all materials induced cytotoxic effects at concentrations of 0.1 mg/mL (p < 0.05), while no significant differences were detected among them. The tested materials revealed no estrogenic activity. All dental monomers and Bisphenol A showed concentration dependent cytotoxic effects (p < 0.05), whereas only Bisphenol A induced an estrogenic effect (p < 0.01). Significance: Dust and eluates of resin-based dental materials released into wastewater exert bactericidal and cytotoxic effects in vitro. However, they reveal no estrogenic effect.